Highly polished pre-hardened plastic mold steel and method of making same
Patent Information
- Application Number
- CN202310578208.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-05-22
AI Technical Summary
此款料的抛光性优异,具有良好的硬度均匀性和机加工性,但韧性较差,模具在使用过程中易开裂,而且限于这款料只能做到400mm以下的厚度,故而无法制作400mm以上的大尺寸模具
[0039]1、本发明降低了贵金属元素Ni的含量(从1.0%以上降低至0.55-0.65%),节省了合金成本;另外,为了提高钢材的淬透性和强度,本发明增加了Cr的含量(从1.25%左右提升至1.75%~1.85%),极大地增加了钢材使用厚度,而且,本发明还增加了V元素(从0.12%以下提升至0.27%-0.32%),以达到细化晶粒、提高钢的强度、改善钢材抛光性能的作用;
Smart Images

Figure CN116716540B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of alloy steel technology, and in particular to a high-polish pre-hardened plastic mold steel and its preparation method. Background Technology
[0002] Molds are the mother of manufacturing; their quality determines the quality of the product. With the booming development of the automotive, home appliance, and other 3C industries, the demands for product quality and cost are increasing, leading to higher requirements for mold steel quality and mold production cycles. In recent years, my country's plastic mold production has continued to rise, accounting for as much as 45% of the mold industry market share. Major application areas include common exterior parts such as bumpers, dashboards, and door panels in the automotive industry; high-requirement optical parts such as pillar trim, headlight lenses, and lamp covers; and products like mouse mice, television casings, and air conditioner panels in the home appliance industry. These molds require good processing performance, short manufacturing cycles, excellent etching and polishing properties, and, most importantly, a longer lifespan.
[0003] In recent years, most of the pre-hardened plastic mold steel materials widely used in the market have been improved based on AISI P20 and P21 types. While ensuring machinability, the content of alloying elements is added or adjusted, and the heat treatment method is improved in order to improve the hardness and hardenability of the material, thereby improving the polishing and etching performance of the mold steel material and extending the service life of the mold.
[0004] The "Pocket World Steel Grade Handbook" by Lin Huiguo, Lin Gang, and Ma Yuehua et al. specifies the chemical composition range of AISI P20 alloy tool steel as follows: C 0.28–0.40%, Si 0.20–0.80%, Mn 0.60–1.00%, P 0.000–0.030%, S 0.000–0.030%, Cr 1.40–2.00%, Mo 0.30–0.55%, with residual Cu and Ni content ≤0.75%, and the remaining elements being Fe and unavoidable impurities. After low-temperature tempering and carburizing at 150–260℃, the surface hardness of this material can reach 64–58 HRC. However, this material has poor hardenability, and overall heat treatment cannot achieve a high service hardness, failing to meet the requirements for high-life pre-hardened plastic mold steel.
[0005] Publicly available information on AISI P20 modified materials imported from Sweden shows that its typical chemical composition is: C 0.26%, Mn 1.45%, S 0.002%, Cr 1.25%, Mo 0.60%, V 0.12%, Ni 1.05%, and it is supplied in a hardened and tempered state to a hardness of HB310-355HB (approximately 33-38HRC). Compared with existing P20 materials, it has increased Mn content, added alloying elements Ni and V, Mo content at the upper limit, and Cr content at the lower limit, which improves the hardenability of the material and provides good polishing and texturing properties. However, the hardness of this material is relatively low, which cannot well meet the requirements for long service life of molds.
[0006] Publicly available information on AISI P20 modified materials imported from Germany shows that its typical chemical composition is C 0.30%, Si 0.30%, Mn 1.55%, Cr 1.35%, Mo 0.70%, and Ni 1.00%. The supplied condition is: hardened and tempered to a hardness of 38–42 HRC. Its non-metallic inclusions (purity) are rated according to standard GB / T 10561-2005, method A, with acceptable ranges as follows: A (sulfides) ≤ 0.5 (length < 127 μm, width < 12 μm), B (oxides) ≤ 1.0 (length < 184 μm, width < 15 μm), C (silicates) ≤ 1.0 (length < 176 μm, width < 12 μm), D (spherical oxides) ≤ 1.0 (diameter < 13 μm, number < 9). Compared to existing P20 grade materials, this material has increased Ni alloying element, improved Mn and Mo content, and reduced Cr content, delivering a hardness range of 38–42 HRC. This higher hardness meets the requirements for long-life molds. However, the purity tolerance range is relatively lenient, with B and C inclusions within the range of 1.0, increasing the likelihood of pitting during polishing. Furthermore, the material exhibits poor micro-area hardness uniformity and insufficient grain refinement, making it prone to material segregation, which negatively impacts polishability and etching performance.
[0007] Publicly available information on AISI P21 modified material imported from Japan shows that its typical chemical composition is: C 0.15%, Si 0.30%, Mn 1.50%, Mo 0.30%, Ni 3.00%, Cu 1.00%, Al 1.00%. The factory hardness is 37–43 HRC, and the hardening method is aging pre-hardening. Compared to existing P21 materials, it reduces the C content, increases the Mn and Ni content, adds alloying elements Cu, Al, and Mo, and removes the alloying element Cr. This material has excellent polishability, good hardness uniformity, and machinability, but poor toughness, making molds prone to cracking during use. Furthermore, this material is limited to thicknesses below 400 mm, thus preventing the production of large-size molds exceeding 400 mm.
[0008] The quality of domestically produced P20 improved materials has greatly improved in recent years, and the price is also quite advantageous compared to imported materials. In many aspects, it can replace the corresponding imported materials. However, in application fields with high polishing requirements, imported materials still have a place, and domestic materials cannot completely replace them.
[0009] In conclusion, my country still has much room for improvement in the field of high-polish pre-hardened plastic mold steel. While maintaining our existing advantages of localization and low cost, we should continue to tackle technological challenges and improve the quality of plastic mold steel in my country. Summary of the Invention
[0010] The purpose of this invention is to provide a high-polish pre-hardened plastic mold steel, which improves the life of the mold steel by adjusting the hardness and impact toughness of the mold steel through chemical composition design.
[0011] The present invention also provides a method for preparing the high-polish pre-hardened plastic mold steel, wherein the method improves the material’s microstructure segregation and hardness uniformity by improving the smelting and forging process, thereby enabling the material to obtain excellent polishing performance, uniform hardness and good impact toughness.
[0012] The objective of this invention is achieved as follows:
[0013] A high-polish pre-hardened plastic mold steel, wherein the composition of the high-polish pre-hardened plastic mold steel by weight percentage is: C 0.33-0.36%, Si 0.20-0.30%, Mn 0.93-1.00%, P 0.00-0.015%, S 0.000-0.002%, Cr 1.75-1.85%, Ni 0.55-0.65%, Mo 0.67-0.72%, V 0.27-0.32%, Cu 0.40-0.50%, H 0.00ppm-2.00ppm, with the balance being Fe and unavoidable impurities.
[0014] Preferably, the composition of the high-polish pre-hardened plastic mold steel, by weight percentage, is as follows:
[0015] C 0.34–0.36%, Si 0.24–0.28%, Mn 0.94–0.96%, P 0.000–0.012%, S 0.000–0.002%, Cr 1.79–1.82%, Ni 0.57–0.63%, Mo 0.67–0.70%, V 0.29–0.32%, Cu 0.40–0.50%, H 1.00 ppm–1.60 ppm, with the balance being Fe and unavoidable impurities. P and S in the formulation are unavoidable impurities and should be controlled to the lowest possible levels; the values given in the formulation are upper limits.
[0016] Preferably, the main components of the high-polish pre-hardened plastic mold steel, by weight percentage, are: C 0.35%, Si 0.25%, Mn 0.95%, Cr 1.82%, Ni 0.60%, Mo 0.70%, V 0.30%, Cu 0.45%.
[0017] Preferably, the hardness range of the mold steel is 40-43 HRC (surface), the core hardness is ≥38 HRC, and the difference in hardness between the core and surface of the steel block does not exceed 10%.
[0018] Preferably, the non-metallic inclusions are rated according to GB / T 10561-2005, Method A, and meet the following conditions: A (sulfides) ≤ 0.5 grade (length < 127 μm, width < 12 μm), B (oxides) ≤ 0.5 grade (length < 77 μm, width < 15 μm), C (silicates) ≤ 0.5 grade (length < 76 μm, width < 12 μm), D (spherical oxides) ≤ 1.0 grade (diameter < 13 μm, number < 4), and DS type (large single-particle spherical oxides) non-metallic inclusions have a size ≤ 1.0 grade (diameter < 27 μm).
[0019] Preferably, the steel block thickness is ≤650mm, width is ≤1400mm, and short cross-sectional area is <1.5m². 2 .
[0020] As a preferred option, the ultrasonic testing level of the steel block should be no lower than the E / e level of the Sep 1921 standard.
[0021] A method for preparing the high-polish pre-hardened plastic mold steel, the method comprising the following steps:
[0022] 1) Smelting: The blast furnace iron is smelted in an electric arc furnace, oxygen is blown and dephosphorized, alloy materials are added after tapping, the chemical composition is adjusted to the target chemical composition range of the product in the LF furnace, and white slag is produced for deoxidation and desulfurization. Argon blowing promotes the inclusions to float to the surface and be absorbed by the slag.
[0023] 2) Vacuum degassing (VD or RH): Vacuum refining, argon degassing at a vacuum of 66.66 Pa or below, with a vacuum holding time of not less than 20 min, to reduce the hydrogen content in the molten steel, while further desulfurizing and removing inclusions;
[0024] 3) Ingot casting: The casting process is carried out by bottom casting with strict control. The casting temperature is 1535~1550℃, and the steel ingot is obtained after casting.
[0025] 4) Free forging in three directions: length, width and thickness: Before forging, the steel ingot is heated to 1215℃~1230℃ in stages, with at least two upsetting and two drawing, forging ratio ≥5.0, final forging temperature 850~900℃, and steel block is obtained after forging.
[0026] 5) Rough machining: After forging, the head and tail of the steel block are cut off and the metallographic structure is tested;
[0027] 6) Post-forging heat treatment: After forging, the module is air-cooled or air-cooled to 350-400℃, then heated to 870-880℃ and held for 10-20 hours. After that, it is air-cooled or air-cooled to 325-375℃. Then it is loaded into the furnace for hydrogen diffusion annealing. After annealing, the module surface is inspected and flaw detection is performed.
[0028] 7) Pre-hardening quenching: The steel block obtained in step 6) is heated to 880-900℃, held for 10-20 hours, and then quenched to 150℃±10℃ for tempering.
[0029] 8) Pre-hardening tempering: Heat the steel block obtained in step 7) to 585-600℃ for the first tempering. The holding time is calculated based on the module thickness and controlled at 10-20 hours. After the furnace temperature is cooled to 450℃±10℃, air cool to room temperature. Then check whether there are cracks or other defects in the appearance of the steel block after the first tempering, and whether the deformation is too large. Check and record the hardness after the first tempering as the basis for setting the second tempering process.
[0030] The steel block is heated to 545-590℃ for a second tempering. The holding time is calculated based on the module thickness and controlled to be 10-20 hours. The testing method after the first tempering is repeated.
[0031] As a preferred embodiment, in step 4), the steel ingot is heated to 1220°C in stages, and the final forging temperature is 880°C.
[0032] 6) After forging, the module is air-cooled or air-cooled to 370°C, then reheated to 875°C, and air-cooled or air-cooled to 350°C.
[0033] In step 7), the steel block obtained in step 6) is heated to 890°C and then quenched to 150°C for tempering.
[0034] In step 8), the steel block obtained in step 7) is heated to 590°C for the first tempering, cooled to 450°C in the furnace, and then air-cooled to room temperature; the steel block is then heated to 560°C for the second tempering.
[0035] Preferably, in steps 6), 7), and 8), the holding time mainly depends on the thickness of the steel block; for every 25 mm increase in steel block thickness, the holding time increases by 1 hour. This preparation method, while achieving the chemical composition and performance parameters required by this invention, can control costs.
[0036] Preferably, in steps 6), 7), and 8), the specific heat preservation time for different steel block thicknesses is as follows:
[0037]
[0038] Compared with the prior art, the beneficial effects of the present invention are:
[0039] 1. This invention reduces the content of the precious metal element Ni (from over 1.0% to 0.55-0.65%), saving alloy costs. In addition, to improve the hardenability and strength of the steel, this invention increases the content of Cr (from about 1.25% to 1.75%-1.85%), greatly increasing the thickness of the steel. Furthermore, this invention also increases the content of V (from below 0.12% to 0.27%-0.32%) to refine the grains, improve the strength of the steel, and improve the polishing performance of the steel.
[0040] 2. This invention strictly controls the content of impurity elements P and S in steel (P: 0.00-0.015%, S: 0.00-0.002%), keeping them at extremely low levels, in order to improve the purity of steel and thus improve its polishing performance. Attached Figure Description
[0041] Figure 1 This is a photo of the polishing effect of the mold steel sample prepared by this invention using No. 3 diamond paste;
[0042] Figure 2 This is a microscopic image (100x) of the mold steel sample prepared by this invention after polishing with No. 3 diamond paste;
[0043] Figure 3 This is a 50X image of the pre-hardened metallographic structure of the mold steel sample prepared by this invention after polishing with No. 3 diamond paste and then etching with 5% nitric acid alcohol.
[0044] Figure 4 This is a metallographic image (500X) of the pre-hardened state of the mold steel sample prepared by this invention after polishing with No. 3 diamond paste and then etching with 5% nitric acid alcohol. Detailed Implementation
[0045] The technical solution of the present invention will be further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any modifications or alterations made to the present invention will fall within the protection scope of the present invention.
[0046] In this invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used are commercially available or commonly used in the art. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art.
[0047] The design mechanism of this invention is as follows:
[0048] Carbon (C) is the most basic element in steel besides iron. It mainly exists as interstitial atoms, forming solid solutions with other elements to increase the steel's strength, such as ferrite and austenite, both of which contain dissolved carbon. It can also form carbide structures, increasing the steel's hardness and wear resistance, such as cementite (Fe3C). Therefore, the higher the carbon content of steel, the higher its strength and hardness, but the lower its plasticity and toughness. In this invention, the C content ranges from 0.33% to 0.36%, with a target value of 0.35%.
[0049] Silicon (Si) is a common element in steel, used as a reducing agent and desulfurizing agent in the steelmaking process. Therefore, steel typically contains 0.20–0.30% silicon. If the silicon content exceeds 0.50–0.60%, silicon is considered a special alloying element, and this type of steel is called "silicon steel." Silicon significantly improves the elastic limit, yield strength, and tensile strength of steel, making it widely used in the manufacture of heavy-duty spring steel. In quenched and tempered structural steel, silicon not only increases the hardenability but also enhances the steel's resistance to tempering after quenching. Therefore, it is often used as an alloying element in quenched and tempered structural steel and can be used to manufacture high-strength, high-toughness, nickel-free, large-section parts that bear heavy loads. Silicon combined with other alloying elements such as molybdenum, tungsten, and chromium improves the steel's corrosion resistance and high-temperature oxidation resistance, and can be used to manufacture nickel-free, low-chromium stainless heat-resistant steel. Low-carbon and ultra-low-carbon steels containing 1.0–4.5% silicon have extremely high magnetic permeability and can be used to make silicon steel sheets for the electrical manufacturing industry. During heat treatment, silicon readily promotes graphitization, leading to decarburization. Therefore, tungsten, vanadium, and chromium are often added to springs to prevent this. It is also used in the manufacture of wear-resistant graphite steel or mold steel. However, high silicon content in steel results in severe spattering during welding, impairing weld quality and increasing cold brittleness. It also enhances the damaging effect of zinc on iron during galvanizing. In this invention, the silicon content ranges from 0.20% to 0.30%, with a target value of 0.25%.
[0050] Mn is a good deoxidizer and desulfurizer, therefore, it is common for steel to contain 0.30-0.50% manganese. When 0.7-1.8% or more manganese is added to carbon steel, it is considered a special "manganese steel". The mechanical properties of carbon steel with a high manganese content are much better than those of steel with a general manganese content. It not only has sufficient toughness (and, under appropriate heat treatment conditions) but also high strength and hardness, improving hardenability and heat treatment processing performance. Therefore, manganese-containing steels have seen rapid development in low-alloy structural steels. The manganese sulfide (MnS) inclusions formed by the combination of manganese and sulfur facilitate chip breakage. Therefore, appropriate amounts of manganese and sulfur can be added to steel to produce free-cutting steel. Furthermore, manganese is widely used in alloy structural steel, spring steel, bearing steel, tool steel, wear-resistant steel, non-magnetic steel, stainless steel, and heat-resistant steel. However, manganese can weaken the corrosion resistance of steel and has an adverse effect on its weldability. In this invention, the manganese content ranges from 0.93% to 1.00%, with a target value of 0.95%.
[0051] P: Under normal circumstances, phosphorus is a harmful element in steel, increasing its cold brittleness, worsening its weldability, reducing its plasticity, and impairing its cold bending performance. Therefore, high-quality steel is usually required to have a phosphorus content of less than 0.030%. However, on the other hand, the higher sulfur and phosphorus content in low-carbon steel can make it easier to cut, which is beneficial for improving the machinability of the steel. In this invention, the phosphorus content is controlled within 0.015%.
[0052] Sulfur (S) is generally considered one of the harmful residual elements in steel. It reduces the ductility and toughness of steel, impairs its corrosion resistance, and has an adverse effect on welding. Therefore, in high-quality steel, its content is controlled below 0.030%. However, under certain conditions, the harmful effects can be transformed into benefits. For example, in sulfur-containing free-machining steel, increasing the sulfur and manganese content leads to the formation of more manganese sulfide (MnS) particles, thereby improving the machinability of the steel. In this invention, the S content is controlled below 0.002%.
[0053] Cr: Adding chromium to steel significantly improves its oxidation resistance, increases its corrosion resistance, and enhances its strength and wear resistance. Because chromium improves the mechanical and physical properties of steel, it is commonly found in varying amounts in alloy steels for various applications. Given the limited chromium resources in my country, its use should be minimized, especially in mass-produced structural steels where its use should be reduced or eliminated altogether. In this invention, the chromium content ranges from 1.75% to 1.85%, with a target value of 1.82%.
[0054] Ni (Ni): Strengthens steel, improves its low-temperature performance, especially its toughness, and enhances its hardenability. Nickel steel also exhibits strong rust resistance and high resistance to corrosion from acids, alkalis, and seawater. However, it has no significant effect on corrosion resistance to oxygen media under high temperature and pressure, and may even cause decarburization, promoting corrosion and cracking. Generally, nickel is not added to domestically produced low-alloy structural steel. At high nickel content, it can significantly alter some physical properties of steel and alloys. However, nickel is an important strategic material and is relatively scarce worldwide. Therefore, as an alloying element in steel, nickel should only be considered when other elements cannot achieve the required properties. Examples include structural steel requiring high strength and high toughness for important applications, steel requiring high toughness under low-temperature operating conditions, high-alloy chromium-nickel austenitic stainless steel, and steel requiring special physical properties. In this invention, the nickel content ranges from 1.55% to 0.65%, with a target value of 0.60%.
[0055] Molybdenum (Mo) is a valuable alloying element, abundant in my country, but not rich in reserves worldwide. Its role in steel can be summarized as improving hardenability and hot strength, preventing temper brittleness, increasing remanence and coercivity, and enhancing corrosion resistance and preventing pitting corrosion in certain media (such as hydrogen sulfide, ammonia, carbon monoxide, and water). Therefore, it is widely used in a range of steel types, including structural steel, spring steel, bearing steel, tool steel, stainless acid-resistant steel, heat-resistant steel (also known as heat-strength steel), and magnetic steel. In many cases, chromium-molybdenum steel can replace the more expensive chromium-nickel steel in manufacturing various important machine parts. However, because molybdenum increases the hot strength of steel, a higher molybdenum content also increases the difficulty of hot working. In this invention, the molybdenum content ranges from 0.67% to 0.72%, with a target value of 0.70%.
[0056] Vanadium (V) is one of the richest elements in my country and one of the most commonly used alloying elements in the development of new steel grades. It has a strong affinity for carbon, nitrogen, and oxygen, forming corresponding, extremely stable compounds. Small amounts (less than 0.5%) of vanadium can refine grains, improve the strength, yield strength ratio, and low-temperature toughness of steel, thus improving its performance and increasing its hot strength and creep resistance. Furthermore, vanadium's carbon-fixing effect can improve the steel's resistance to hydrogen corrosion at high temperatures. However, vanadium always needs to be used in combination with other alloying elements such as manganese, chromium, tungsten, and molybdenum. It is commonly used in low-temperature steels, high-pressure hydrogen-resistant steels, high-quality spring steels, new bearing steels, alloy tool steels, high-speed tool steels, and heat-resistant steels. However, the vanadium content should not be too high, as this reduces the steel's toughness. In this invention, the vanadium content range is set at 0.27%–0.32%, with a target value of 0.30%.
[0057] Cu (Cu): Adding 0.20–0.50% copper to steel, especially when used in combination with phosphorus, can give low-alloy steel and rail steel excellent resistance to atmospheric corrosion. It also helps improve the steel's strength, wear resistance, and yield strength ratio, without adversely affecting its weldability. It is currently the main type of steel used in the construction of bridges, ships, automobiles, locomotives, chemical and petroleum equipment, and high-pressure vessels. Adding 2–3% copper to austenitic stainless steel can improve its corrosion resistance in acidic media. However, copper is a scarce metal and a strategic resource, so it should generally not be intentionally added during the refining process. Since copper in steel cannot be removed during the smelting process, and my country has abundant copper-bearing iron ore, copper-bearing iron ore can be used to develop copper-containing steel. The Cu content added in this invention ranges from 0.40–0.50%, with a target value of 0.45%.
[0058] Hydrogen (H): Dissolves in steel in atomic or ionic form, forming interstitial solid solutions, thus playing a role in alloying and stabilizing austenite, increasing the hardenability of steel. However, it also causes many serious defects, such as white spots, point segregation, hydrogen embrittlement, and cracks in the heat-affected zone of welds. Therefore, it is generally considered a harmful element, and various measures are taken to reduce its content in steel. Therefore, this invention controls the H content to below 2 ppm.
[0059] In addition to ensuring that the chemical composition meets the required range, other performance parameters of this invention must also be controlled within acceptable ranges. The rationale for designing the performance parameters of this invention is as follows:
[0060] Hardness: Previously, materials with lower hardness often cracked during use due to insufficient wear resistance or strength, thus failing to reach their expected lifespan. Therefore, this is addressed by increasing hardness. This invention increases the hardness from below 40 HRC to 40-43 HRC (surface), while setting the core hardness above 38 HRC. Furthermore, to ensure consistent core hardness, the difference in hardness between the core and surface of the steel block must not exceed 10%.
[0061] Ultrasonic testing: Ultrasonic testing is a type of non-destructive testing used to detect internal defects in materials to ensure their quality. In this invention, the ultrasonic testing qualification level for the material is set as Sep1921, E / e grade, to further ensure the material's quality upon leaving the factory.
[0062] Non-metallic inclusions: A general term for various non-metallic particles embedded in steel. The five main categories that significantly affect steel properties are A (sulfides), B (oxides), C (silicates), D (spherical oxides), and DS (single-particle spherical inclusions). Inclusions of different forms mixed within steel disrupt its continuity and integrity, reducing its strength, toughness, fatigue resistance, and especially its polishability. Therefore, in this invention, the acceptable levels for the five types of inclusions are set according to GB / T10561-2005, Method A: A≤0.5 (length <127µm, width <12µm), B≤0.5 (length <77µm, width <15µm), C≤0.5 (length <76µm, width <12µm), D≤1.0 (diameter <77µm, number <9), and DS≤1.0 (diameter <27µm).
[0063] Steel block dimensions: The mold size determines the product size, and some products cannot be produced due to limitations in mold size. This invention designs the product dimensions as follows: steel block thickness ≤ 650mm, width ≤ 1400mm, and short cross-sectional area < 1.5m². 2 This range refers to the upper limit of the product obtained by this invention; that is, this invention can prepare steel blocks smaller than this size.
[0064] Examples 1-5 and Comparative Examples 1-2
[0065] A method for preparing a high-polish pre-hardened plastic mold steel, after confirming the requirements of the steel technical specifications, and ensuring the availability of steelmaking raw materials and equipment, includes the following specific steps:
[0066] 1) Smelting: Electric arc furnace smelting, oxygen blowing and desulfurization, after tapping the steel, add alloy materials such as ferromolybdenum, ferrochrome, pure nickel, ferrovanadium, and copper plate, adjust the chemical composition content to the target chemical composition range of the product in the LF furnace. The element formula of the mold steel in each embodiment is shown in Table 1. White slag is produced for deoxidation and desulfurization, and argon blowing promotes the inclusions to float to the surface and be absorbed by the slag.
[0067] 2) Vacuum degassing (VD or RH): Vacuum refining, argon degassing at a vacuum of 66.66 Pa or below, with a vacuum holding time of not less than 20 min, to reduce the hydrogen, oxygen and nitrogen content in the molten steel to extremely low levels, while further desulfurizing and removing inclusions;
[0068] 3) Ingot casting: The casting process is carried out by bottom casting with strict control of the casting temperature, which is 1535~1550℃;
[0069] 4) Free forging in three directions: length, width and thickness: Before forging, the steel ingot is heated to 1215℃~1230℃ in stages, with at least two upsetting and two drawing, forging ratio ≥5.0, and final forging temperature ≤900℃;
[0070] 5) Rough machining: After the steel block is forged, the head and tail of the steel block are cut off and the metallographic structure is tested.
[0071] 6) Post-forging heat treatment: After forging, the module is air-cooled or air-cooled to 350-400℃, then heated to 870-880℃ and held for 10-20 hours. After that, it is air-cooled or air-cooled to 325-375℃. Then it is loaded into the furnace for hydrogen diffusion annealing. After annealing, the module surface is inspected and flaw detection is performed.
[0072] 7) Pre-hardening quenching: The steel block obtained in step 6) is heated to 880-900℃, held for 10-20 hours, and then quenched to 150℃±10℃ for tempering.
[0073] 8) Pre-hardening tempering: Heat the steel block obtained in step 7) to 585-600℃ for the first tempering. The holding time is calculated according to the thickness of the module. After the furnace temperature is cooled to 450℃±10℃, it is air-cooled to room temperature. Then, check whether there are cracks or other defects in the appearance of the steel block after the first tempering, and whether the deformation is too large. Check and record the hardness after the first tempering as the basis for setting the second tempering process.
[0074] The steel block is heated to 545-590℃ for a second tempering. The holding time is calculated based on the module thickness. The testing method after the first tempering is repeated.
[0075] The heat preservation time in steps 6), 7), and 8) is mainly set according to the thickness of the steel block, and the specific scheme is shown in Table 2.
[0076] Table 1. Composition (wt%) of the high-polish pre-hardened plastic mold steel obtained in the embodiments of the present invention.
[0077]
[0078] Note: The component content balance in Table 1 is Fe, and the total is 100wt%.
[0079] In order to obtain the target hardness range, the heat treatment process parameters in Table 2 were used to heat treat the steel blocks obtained in step 6) of each embodiment, namely the specific parameters of pre-hardening quenching in step 7) and pre-hardening tempering in step 8). By slowly heating the steel blocks to the microstructure transformation temperature and holding them at that temperature for a long time, the steel blocks obtained the uniform hardness shown in Table 3.
[0080] Table 2 Heat treatment process parameters for steel in each embodiment
[0081]
[0082] The dimensions, weight, hardness measurements, and ultrasonic testing results of the high-polish pre-hardened plastic mold steels prepared in each embodiment are shown in Table 3. The maximum thickness of the steel in the embodiments is 500 mm, which can meet the requirements of large-size molds; the hardness test values of the embodiments are all in the range of 40-43 HRC, which meets the design standards; the ultrasonic testing results of the embodiments all meet the E and e grades.
[0083] Table 3. Test values of steel dimensions, weight, hardness, and ultrasonic testing results in the examples.
[0084] 1 245 910 7220 414141 E / e level 2 290 710 7400 404140 E / e level 3 440 1150 11280 414242 E / e level 4 330 710 5800 424141 E / e level 5 500 1050 11240 404041 E / e level Comparative Example 1 280 850 9540 414141 E / e level Comparative Example 2 550 810 10500 414241 E / e level
[0085] Note:
[0086] ① The hardness testing standard is GB230.1-2018, and the hardness testing equipment is a magnetic Rockwell hardness tester produced by Shenyang Tianxing, model PHR-100.
[0087] ② The ultrasonic flaw detection standard is SEP1921-1984, and the ultrasonic testing equipment is the HS500 digital ultrasonic flaw detector manufactured by Hanwei.
[0088] The non-metallic inclusion detection results for each embodiment are shown in Table 4. Figures 1-4 ,in Figure 1 The image shows the effect after polishing the sample with diamond paste No. 3. The sample surface has no obvious impurities or lines, indicating a good polishing effect. Figure 2 The morphology observed under a metallographic microscope after polishing with #3 diamond paste and magnified 100 times is shown. It can be seen that there are no obvious inclusions on the sample surface, and the inclusion content of this material is within the qualified range. Figure 3 and Figure 4 The images represent the low-magnification (50X) and high-magnification (500X) metallographic structures observed under a metallographic microscope after the samples were polished with #3 diamond paste and then etched with 5% nitric acid alcohol. It can be seen that there is no obvious banded segregation on the sample surface, and the sample structure is uniform and fine, indicating that this material can be used to make molds with high polishing requirements.
[0089] Table 4. Non-metallic inclusion detection results for each embodiment. Test standard: GB / T 10561-2005, A
[0090]
[0091] Note: Non-metallic inclusion samples were all taken from the core of the dry steel block, and the preparation process involved inlaying, grinding, and polishing. They were examined using a motic-BA310Met metallographic microscope manufactured by McAudio.
[0092] As shown in Table 4, the non-metallic inclusion content in each embodiment was controlled at a very low level. The four types of non-metallic inclusions, A (sulfides), B (alumina), C (silicates), and DS (single-particle spherical oxides), were not detected. The content of D (single-particle spherical inclusions) was controlled below level 1.0. Moreover, the test samples were taken from the core of the base material, where the quality was the most difficult to control.
[0093] In summary, this invention achieves its goals by rationally designing the chemical composition range of the steel block: for example, reducing the content of the precious metal element Ni (from over 1.0% to 0.55-0.65%), thus saving alloy costs; increasing the Cr content (from around 1.25% to 1.75%-1.85%) to improve the hardenability and strength of the steel, thereby significantly increasing the thickness of the steel; increasing the V element (from below 0.12% to 0.27%-0.32%) to refine the grains, improve the strength of the steel, and enhance its polishing performance; and by strictly controlling the steel smelting process, keeping the content of impurity elements P and S (P: 0.00-0.015%, S: 0.00-0.002%) in the steel at extremely low levels, thereby improving the purity of the steel and thus enhancing its polishing performance.
[0094] The above examples also show that the chemical composition of the steel blocks produced by the method of the present invention is within the qualified range; and after heat treatment, the measured hardness values of the steel blocks are all within the range of 40-43 HRC, with uniform hardness; after the steel blocks are smelted, the ultrasonic flaw detection results also meet the design requirements, and the non-metallic inclusion grades of the steel blocks are all within the qualified range, and the steel exhibits excellent purity; the metallographic structure of the steel is also very uniform and fine, with no obvious structural segregation, so this material can be used for products with high polishing requirements.
[0095] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on its differences from other embodiments. Similar or identical parts between embodiments can be referred to interchangeably. For the apparatus disclosed in the embodiments, since it corresponds to the method disclosed in the embodiments, the description is relatively simple; relevant parts can be referred to in the method section.
[0096] The high-polish pre-hardened plastic mold steel and its preparation method provided by this invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this invention. It should be noted that those skilled in the art can make several improvements and modifications to this invention without departing from the principles of this invention, and these improvements and modifications also fall within the protection scope of the claims of this invention.
Claims
1. A high-polish pre-hardened plastic mold steel, characterized in that... The composition of the high-polish pre-hardened plastic mold steel, by weight percentage, is as follows: C 0.33~0.36%, Si 0.20~0.30%, Mn 0.93~1.00%, P 0.000~0.015%, S 0.000~0.002%, Cr 1.75~1.85%, Ni 0.55~0.65%, Mo 0.67~0.72%, V 0.27~0.32%, Cu 0.40~0.50%, H 0.00ppm~2.00ppm, balance Fe and unavoidable impurities.
2. The high-polish pre-hardened plastic mold steel according to claim 1, characterized in that... The composition of the high-polish pre-hardened plastic mold steel, by weight percentage, is as follows: C 0.34~0.36%, Si 0.24~0.28%, Mn 0.94~0.96%, P 0.000~0.012%, S 0.000~0.002%, Cr 1.79~1.82%, Ni 0.57~0.63%, Mo 0.67~0.70%, V 0.29~0.32%, Cu 0.40~0.50%, H 1.00ppm~1.60ppm, balance Fe and unavoidable impurities.
3. The high-polish pre-hardened plastic mold steel according to claim 1, characterized in that: The composition of the high-polish pre-hardened plastic mold steel, by weight percentage, is: C 0.35%, Si 0.25%, Mn 0.95%, P 0.000~0.015%, S 0.000~0.002%, Cr 1.82%, Ni 0.60%, Mo 0.70%, V 0.30%, Cu 0.45%, H 0.00ppm~2.00ppm, with the balance being Fe and unavoidable impurities.
4. The high-polish pre-hardened plastic mold steel according to claim 1, characterized in that: The surface hardness of the mold steel is in the range of 40~43HRC, the core hardness is ≥38HRC, and the difference between the core and surface hardness of the mold steel does not exceed 10%.
5. The high-polish pre-hardened plastic mold steel according to claim 1, characterized in that: Non-metallic inclusions shall be rated according to GB / T 10561-2005, Method A, and shall meet the following conditions: A≤0.5 grade, B≤0.5 grade, C≤0.5 grade, D≤1.0 grade, and the size of non-metallic inclusions of DS class shall be ≤1.0 grade.
6. The high-polish pre-hardened plastic mold steel according to claim 1, characterized in that: The thickness of the mold steel is ≤650mm, the width is ≤1400mm, and the short cross-sectional area of the mold steel is <1.5m².
7. The high-polish pre-hardened plastic mold steel according to claim 1, characterized in that: The ultrasonic testing grade of mold steel shall not be lower than the E / e grade of the Sep1921-1984 standard.
8. A method for preparing the high-polish pre-hardened plastic mold steel according to claim 1, characterized in that... The method includes the following steps: 1) Smelting: The blast furnace iron is smelted in an electric arc furnace and oxygen is blown to remove phosphorus. After tapping, alloy materials are added. The chemical composition is adjusted to the target chemical composition range of the product in the LF furnace. White slag is produced for deoxidation and desulfurization. Argon blowing promotes the inclusions to float to the surface and be absorbed by the slag. 2) VD or RH vacuum degassing: vacuum refining, argon degassing at a vacuum degree below 66.66Pa, and holding under vacuum for no less than 20 minutes to reduce the hydrogen content in the molten steel, while further desulfurizing and removing inclusions; 3) Ingot casting: The casting process is carried out by bottom casting with strict control. The casting temperature is 1535~1550℃, and the steel ingot is obtained after casting. 4) Free forging in three directions: length, width and thickness: Before forging, the steel ingot is heated to 1215℃~1230℃ in stages, with at least two upsetting and two drawing, forging ratio ≥5.0, and final forging temperature 850~900℃. After forging, a steel block is obtained. 5) Rough machining: After forging, the head and tail of the steel block are cut off and the metallographic structure is tested; 6) Post-forging heat treatment: After forging, the module is air-cooled or air-cooled to 350-400℃, then heated to 870-880℃ and held for 10-20 hours. After that, it is air-cooled or air-cooled to 325-375℃, and then loaded into the furnace for hydrogen diffusion annealing. After annealing, the module surface is inspected and flaw detection is performed. 7) Pre-hardening quenching: The steel block obtained in step 6) is heated to 880~900℃, held for 10~20 hours, and then quenched to 150℃±10℃ for tempering. 8) Pre-hardening tempering: Heat the steel block obtained in step 7) to 585~600℃ for the first tempering. The holding time is calculated based on the module thickness and controlled at 10~20 hours. After the furnace temperature is cooled to 450℃±10℃, air cool to room temperature. Then check whether there are cracks or defects in the appearance of the steel block after the first tempering, and whether the deformation is too large. Check and record the hardness after the first tempering as the basis for setting the second tempering process. The steel block is heated to 545~590℃ for a second tempering. The holding time is calculated based on the module thickness and controlled at 10~20 hours. The testing method after the first tempering is repeated.
9. The preparation method according to claim 8, characterized in that: 4) In the process, the steel ingot is heated to 1220℃ in stages, and the final forging temperature is 880℃; 6) After forging, the module is air-cooled or air-cooled to 370°C, then reheated to 875°C, and air-cooled or air-cooled to 350°C. In step 7), the steel block obtained in step 6) is heated to 890°C and then quenched to 150°C for tempering. In step 8), the steel block obtained in step 7) is heated to 590°C for the first tempering, cooled to 450°C in the furnace, and then air-cooled to room temperature; the steel block is then heated to 560°C for the second tempering.
10. The preparation method according to claim 8, characterized in that: In steps 6), 7), and 8), the heat preservation time mainly depends on the thickness of the steel block. For every 25mm increase in the thickness of the steel block, the heat preservation time increases by 1 hour.
Citation Information
Patent Citations
Plastic mould steel and manufacturing method thereof
CN107974623A